Composition of chemical elements in the edible viscera of Tibetan pigs and its correlation with environment and feed. (March 2020) - Mi, Si; Shang, Ke; Jia, Wei; Zhang, Chun-Hui; Liu, Ji-Qian; Huang, De-Qiong
Graphical abstract: Highlights: A panel of 55 chemical elements was simultaneously quantified in this work. P, K, Na, Mg, Ca, Fe and Zn were the most abundant elements in the viscera. Liver and kidney were the two richest organs of chemical elements. Tibetan pig viscera were not fully fit for consumption as food. Element profile of viscera is significantly correlated with feed, soil and water. Abstract: The main purpose of this research was to evaluate the element distribution in the edible viscera of Tibetan pigs and to clarify its correlation with soils, drinking water and feed. A total of 55 chemical elements were simultaneously quantified. P, K, Na, Mg, Ca, Fe and Zn were the most abundant elements in the analyzed viscera. The general distribution of all element concentrations in the viscera of Tibetan pigs was such that liver > kidney > small intestine > heart = lung = large intestine > stomach. Comparison with national and international allowable limits of toxic elements indicates that consumption of Tibetan pig viscera presents potential health risks. Spearman correlation analysis reveals that significantly ( p  < 0.0001) positive relationships exist between the element profiles of viscera and drinking water, soils as well as feed. For all edible viscera, the largest values of correlation coefficient were observed to be with corn feed. Our research provides a relatively comprehensive investigation of the elemental composition in Tibetan pig viscera. The correlation data would be helpful for the local farm to reformulate the feed for Tibetan pigs to improve the quality and safety of the viscera.